2014
DOI: 10.1590/s2317-15372014000100004
|View full text |Cite
|
Sign up to set email alerts
|

Seed quality of rice cultivars stored in different environments

Abstract: -The objective of this study was to evaluate dormancy and physiological quality of seeds of rice cultivars during storage in different environments. After harvesting, the seeds of three rice cultivars (Seleta, Curinga and Relâmpago) were dried in the sun, to reach moisture content at around 13%. Then, they were packed in paper and stored in four environments: 5 ± 2 °C / 70 ± 5% RH, 12 ± 2 °C / 70 ± 5% RH, 18 ± 2 °C / 65 ± 5% RH and in uncontrolled condition of temperature and relative humidity (natural). Physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
3
6
0
3
Order By: Relevance
“…Marques et al (2014) have observed similar results studying three rice cultivars stored in four storage environments, namely, loss of germination vigor after reaching maximum germination and vigor. Macedo et al (1999) when assessing rice seeds of cultivar IAC 165, stored for 12 months in Campinas, SP, with a relative humidity of 72% and an average temperature of 21 °C, have observed a gradual decrease in germination from the eighth month.…”
Section: Resultssupporting
confidence: 61%
“…Marques et al (2014) have observed similar results studying three rice cultivars stored in four storage environments, namely, loss of germination vigor after reaching maximum germination and vigor. Macedo et al (1999) when assessing rice seeds of cultivar IAC 165, stored for 12 months in Campinas, SP, with a relative humidity of 72% and an average temperature of 21 °C, have observed a gradual decrease in germination from the eighth month.…”
Section: Resultssupporting
confidence: 61%
“…Some authors questioned the ability of EC test for seed deterioration monitoring in 4 8 9 *Means with the same letter in each column do not differ by LSD Fisher (p<0.05), G: Germination, EC: Electrical conductivity and TZ-V: High vigor seeds by tetrazolium at low temperature, suggesting that stabilization of membrane occurs, which results in lower leakage of exudates (Fessel et al, 2010). Contrarily other authors recommended this test for vigor evaluation even at low temperature storage (Panobianco et al, 2007;Mielezrski and Marcos-Filho, 2013;Marques et al, 2014). In our experiments, a greater sensitivity of high oleic G3 on the electrolytes leaching was observed in storage at 10°C (Fig.…”
Section: Resultssupporting
confidence: 64%
“…Drying and storage comprise some of the main processes in the rice seeds production since they provide their conservation until sowing in the next crop. However, when poorly handled, these processes can significantly alter the seed quantitative and qualitative characteristics (Marques et al, 2014a;Scariot et al, 2018).…”
Section: Introductionmentioning
confidence: 99%